أثر تخطيط المسار الوظيفي على جودة حياة العمل: دراسة تطبيقية على العاملين الإداريين بجامعات وسط الدلتا - عبدالسلام، رمضان محمود; أبو العطا، سناء أحمد حسنين; الطبلاوي، أسامة السيد أحمد (جامعة كفر الشيخ - كلية التجارة, 2019)
Aim: This study aims to investigate the impact of career planning on quality of work-life using a sample of administration employees from Central Delta universities (Tanta University, Kafrelsheikh University, and Menoufia University). Method: to achieve the study aims, the researcher developed a questionnaire answered by a sample of (380) participants. The researcher retrieved only (321) of the answered questionnaires, and excluded (21) because of incomplete, unclear, or missing answers. The researcher used several statistical techniques in this study (e.g. Median, Correlation Coefficient, Multiple Regression, Exploratory Factor Analysis, Variance Analysis, Cronbach's Alpha, and T-Test) using (SPSS v.18) program. Results: the present study showed that there is a statistically significant impact for career planning on quality of work-life.
الأهداف: استهدف هذا البحث التعرف على أثر تخطيط المسار الوظيفي على جودة حياة العمل بالتطبيق على العاملين الإداريين بجامعات وسط الدلتا (جامعة طنطا، وجامعة كفر الشيخ، وجامعة المنوفية). المنهجية: لتحقيق أهداف البحث، تم إعداد استبانة وتوزيعها على عينة مكونة من (380) مفردة، وتم استعادة (321)، ثم استبعاد (21) غير صالحين لعدم استكمال أو عدم وضوح الإجابات. استخدمت الباحثة العديد من الأساليب الإحصائية، باستخدام برنامج (SPSS v.18)، ومنها (الوسط الحسابي، ومعامل الارتباط، والتحليل العاملي الاستكشافي، والانحدار المتعدد، وتحليل التباين، وألفا كرونباخ، واختبار "ت"، واختبار "ف"). النتائج: توصلت نتائج البحث إلى وجود تأثير ذو دلالة إحصائية لتخطيط المسار الوظيفي على جودة حياة العمل.
Keywords: تخطيط المسار الوظيفى -- جودة حياة العمل -- جامعات وسط الدلتا